Pengaruh Perbedaan Budaya Dan Tradisi Dalam Pernikahan Antar Etnis Terhadap Stabilitas Rumah Tangga Di Kota Padangsidimpuan - Harahap, Amhar Maulana (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2024)
This article seeks to explain the impact of cross-ethnic marriage or different ethnicities and cultures between the two parties. With this type of field research research. With direct data sources to the KUA in Padangsidimpuan City and marriage perpetrators. This research shows that the causes of inter-ethnic marriages in Padangsidimpuan City include physical attraction, similarities in work and economy, place of residence, heterogeneous environment, and education. The negative impacts of inter-ethnic marriages in Padangsidimpuan City include differences in communication methods due to language differences, causing misunderstandings and conflicts that lead to divorce. Apart from that, the lack of acceptance between partners in the early stages of marriage, as well as discrimination against each other's ethnicity and customs, also plays a role in reducing household harmony. However, on the positive side, cross-cultural marriages bring opportunities to learn two different communication tools and cultures, enriching the family's experience and understanding of cultural diversity and strengthening family bonds.